Analisis Pengaruh Beban Tak Seimbang Terhadap Arus Netral Pada Trafo IV GI Sukamerindu Bengkulu - Hendro Tanamal; Afriyastuti Herawati; Novalio Daratha; Ika Novia Anggraini (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2019)
ABSTRAKTransformer IV is one of the 20 kV distribution transformers found at the Sukamerindu Bengkulu Substation (GI). The transformer has a power rating of 30 MVA. In distribution transformers, inter-phase load balancing is needed. If the load is not balanced between the phases, current will flow in neutral wire. In this study the effect of unbalanced load on neutral current in transformer IV Sukamerindu Bengkulu is analyzed. The load is analyzed every hour of the day by observing the amount of current and voltage in each phase. From the results of the analysis it was found that the highest neutral current loss value was 1306.25 watts or 1.30 kW and the lowest was 0.724 kW, with an average neutral current loss that occurred in the IV unit transformer Sukamerindu at 639 watts.